2002
DOI: 10.1007/s00330-002-1716-4
|View full text |Cite
|
Sign up to set email alerts
|

Lumbosacral epidural lipomatosis: MRI grading

Abstract: Lumbosacral epidural lipomatosis (LEL) is characterized by excessive deposition of epidural fat (EF). The purpose of our retrospective study was to quantify normal and pathologic amounts of EF in order to develop a reproducible MRI grading of LEL. In this study of 2528 patients (1095 men and 1433 women; age range 18-84 years, mean age 47.3 years) we performed a retrospective analysis of MRI exams. We obtained four linear measurements at the axial plane parallel and tangent to the superior end plate of S1 verte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
148
2
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(162 citation statements)
references
References 41 publications
3
148
2
5
Order By: Relevance
“…In approximately 75% of SEL, this may be secondary to exogenous steroid ad- . Diagnosis is best based on MRI 6,10,15) . T1-WI differentiate epidural fat from dural content with a high degree of specificity and allow for measurement of adipose tissue thickness.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In approximately 75% of SEL, this may be secondary to exogenous steroid ad- . Diagnosis is best based on MRI 6,10,15) . T1-WI differentiate epidural fat from dural content with a high degree of specificity and allow for measurement of adipose tissue thickness.…”
Section: Discussionmentioning
confidence: 99%
“…T1-WI differentiate epidural fat from dural content with a high degree of specificity and allow for measurement of adipose tissue thickness. Definite MRI finding of SEL is the pathognomonic appearance of fat on MRI; high signal intensity on T1-WI, intermediate signal intensity on T2-WI 2,6,9,10,15) . On CT scans, SEL presents as a homogenous hypodense epidural mass with a density between -80 and -160 HU 24) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Borre et al [4] indicated that 86.6% of lipomatosis cases are obese (BMI [ 27.5). In the epidural lipomatosis cases that are seen with obesity, epidural fat can be reduced by low calorie diets [5,13]. But the significant existence of obesity in advanced lipomatosis cases was not determined yet.…”
Section: Discussionmentioning
confidence: 99%